La investigacion en campos de agricultores sobre frijol en la Fraylesca, Chiapas, Mexico:Avances del proyecto La Fraylesca - Villar Sánchez, Bernardo (International Center for Tropical Agriculture, 1987)
Preliminary results from the 1st exptl. cycle of on-farm research in La Fraylesca (Chiapas, Mexico) are summarized. Four kinds of expt. were conducted to evaluate planting time (earliness), N and P doses, var. resistant to diseases, and validation of already generated technology. On the av., no var. performed better than the checks. A difference of 342 kg/ha was observed between the most and least yielding localities. Var. Negro Huasteco was consistently superior to cv. Veracruzano (most common local). Apparently, the 9 introduced var. did not perform better than var. Negro Huasteco. It is possible to anticipate planting times in beans by using early var. like Sesentano. (CIAT)